2018
DOI: 10.1002/ajh.25345
|View full text |Cite
|
Sign up to set email alerts
|

Integrated automated particle tracking microfluidic enables high‐throughput cell deformability cytometry for red cell disorders

Abstract: Investigating individual red blood cells (RBCs) is critical to understanding hematologic diseases, as pathology often originates at the single-cell level. Many RBC disorders manifest in altered biophysical properties, such as deformability of RBCs. Due to limitations in current biophysical assays, there exists a need for high-throughput analysis of RBC deformability with single-cell resolution. To that end, we present a method that pairs a simple in vitro artificial microvasculature network system with an inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…In the initial period of studying the effect of cold-storage on the deformability of PRBCs was carried out using the filtration method (Kucera et al, 1985;Wegner and Kucera, 1989) and ektacytometry (Cluitmans et al, 2012;Sosa et al, 2014;Marin et al, 2021;van Cromvoirt et al, 2021). In the last decade, measurements with a flow chamber (Relevy et al, 2008;Barshtein et al, 2014Barshtein et al, , 2020bOrbach et al, 2017) or microfluidic systems (Guruprasad et al, 2019;Islamzada et al, 2020;Man et al, 2020) have become more frequently used.…”
Section: Cold Storage Of Rbcs and Cell Deformabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the initial period of studying the effect of cold-storage on the deformability of PRBCs was carried out using the filtration method (Kucera et al, 1985;Wegner and Kucera, 1989) and ektacytometry (Cluitmans et al, 2012;Sosa et al, 2014;Marin et al, 2021;van Cromvoirt et al, 2021). In the last decade, measurements with a flow chamber (Relevy et al, 2008;Barshtein et al, 2014Barshtein et al, , 2020bOrbach et al, 2017) or microfluidic systems (Guruprasad et al, 2019;Islamzada et al, 2020;Man et al, 2020) have become more frequently used.…”
Section: Cold Storage Of Rbcs and Cell Deformabilitymentioning
confidence: 99%
“…Research directly targeting unit-to-unit variations in PRBCs deformability has only recently been initiated, with several authors have demonstrated the significance of this phenomenon (Frank et al, 2013;Matthews et al, 2015;Guruprasad et al, 2019;Jeon et al, 2019;Barshtein et al, 2020b;Islamzada et al, 2020;van Cromvoirt et al, 2021). It was found that two factors primarily cause variability among units: the difference in the initial properties of donated RBCs and the differing ability of the cells to retain their deformability during storage (Barshtein et al, 2020b;Islamzada et al, 2020).…”
Section: Unit-to-unit Variability Of Rbc Deformabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, blood cannot be treated as a simple continuum, and it is important to consider the stiffness and size of single blood cells. In the smallest capillaries, RBCs must deform to pass, so changes in microvasculature function and transport occur due to increases in RBC stiffness or adhesion, which is common in many cases, including sickle cell disease ( 16 , 17 ), malaria ( 18 , 19 ), or even various intravenous fluids ( 16 ). Adding to this complexity, the shear ( 20 ) and oxygen levels ( 21 ) in the local microenvironment also affect RBC adhesiveness.…”
Section: The Biology Biophysics and Pathology Of The Microvasculaturementioning
confidence: 99%
“…3 RBC disorders such as sickle cell disease are also associated with increasing cell stiffness -an approximately threefold increase in membrane shear modulus 4 -and a broadening of the cell size distribution. 5 RBCs are examples of natural capsules consisting of a fluid core encapsulated by a semi-permeable membrane. 6 In fact, the transport and flow-induced deformation of RBCs and other biological cells are commonly modelled with idealised capsules and soft beads.…”
Section: Introductionmentioning
confidence: 99%